REFLECTION OF THE BANK’S CREDIT ACTIVITIES IN ACCOUNTING - KLYMENKO, KATERYNA; BELOZERTSEV, VASYL; KHARAKOZ, LILIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the conditions of market economy development the money and money capital markets, the main subjects of which are banks, are of particular importance. First of all, credit institutions are intermediaries in the implementation of settlements between economic entities of market relations. In this regard, the organization of an effective system of accounting for credit activities is one of the urgent tasks of any banking institution, the quality of the solution of which significantly depends on the successful operation of the bank. The article identifies the theoretical features of the reflection of the bank’s lending activities in accounting, analyzes the modern methodology of accounting for credit operations of the bank. An economic and legal analysis of the regulatory framework for lending to a banking institution was conducted. The principles of reflecting the main credit operations of the bank are studied. The organization of effective reflection of the bank’s credit activity, first of all, depends on the principles used by the banking institution in accounting. In particular, such as: prudence, accounting stability, transaction dates, division of reporting periods, valuation of assets and liabilities, separate reflection of assets and liabilities. Accounting for credit activities of the bank refers to the accounting of interest and commission income; accounting for the face value of the loan and changes in the principal amount of debt. Paying attention to the current state of accounting for credit operations, society will require much more information about their activities to restore confidence in banking institutions. This can be achieved through the developed recommendations for improving the method of accounting for credit activities of banks, namely: the introduction of methods for accounting for deferred debt on credit operations, indicating in the Chart of Accounts of banks of Ukraine accounts for deferred debt depending on the date of its occurrence.